An empirical assessment of the financial development: Environmental quality nexus in the European Union - Alexandra Horobet; Irina Mnohoghitnei; Dan Gabriel Dumitrescu; Ştefania-Cristina Curea; Lucian Belascu (Amfiteatru Economic Journal, 2022)
Our study examines the dynamic relationship between financial development and environmental degradation in the European Union (EU) in a panel VAR (Vector Autoregressive) methodological framework over the period 1996-2018. Panel causality tests and impulse response functions show that financial development contributes to higher carbon emissions, although this effect is stronger in the short run and weaker in the long run. At the same time, financial institutions development is the major contributor to fostering increased environmental degradation instead of financial markets, which points towards an engagement of financial institutions towards offering financial products that led to environmental degradation and/or lagging financial markets in terms of promoting environmentally-related securities and ESG principles. By providing new insights into the relationship between financial development and carbon emissions, we hope to assist EU policymakers and businesses in reconsidering the role of financial development as an effective means of decreasing environmental degradation in the region.
Keywords: G20; O13; O44; 330; carbon emissions; EU; Financial development; financial institutions; financial markets; impulse response; panel VAR